DDRE-37. YB-1 AS A BIOMARKER FOR DRUG RESISTANCE AND TUMOUR PROGRESSION IN MEDULLOBLASTOMA. (12th November 2021) - Taylor, Louisa; Kerr, Ian; Coyle, Beth
Abstract: Medulloblastoma (MB) relapse is the most significant unmet clinical challenge in childhood cancer. Recently it has become evident that MBs display altered biology at relapse, indicative of the emergence and expansion of a minor, therapy resistant cancer cell population. Thus, the examination of mechanisms underlying therapy resistance is of critical importance. Y-box binding protein 1 (YB-1) is a multi-functional oncoprotein whose elevated expression and nuclear accumulation correlate with drug resistance, metastasis and disease progression in numerous cancers, although little is known about the functional role of YB-1 in MB. Genomic analysis of large-scale publicly available patient datasets revealed YB-1 expression is significantly elevated across MB molecular subgroups and high expression correlates with poor overall survival. Immunohistochemical analysis of YB-1 localisation in patient TMAs revealed significant YB-1 nuclear accumulation, suggestive of elevated YB-1 nuclear activity in these patients. Treatment of Group 3 MB cell lines (D283MED and HDMB-03) with cisplatin and subsequent analysis by nuclear/cytoplasmic fractionation and confocal microscopy revealed significantly increased nuclear and overall YB-1 expression, indicating a role for YB-1 in cellular stress response. In support of this, ChIP analysis in D283MED and HDMB-03 cell lines confirmed YB-1 interaction with multi-drug transporter gene ABCB1, while stable YB-1 knockdown resulted in significantly reduced ABCB1 expression. Likewise, knockdown of YB-1 expression in D283MED cells results in increased susceptibility of cells to vincristine, supporting a role for YB-1 in the acquisition of drug resistance in MB cell lines. Finally, whole transcriptome sequencing of YB-1-knockdown HDMB-03 and D283MED cell lines indicated YB-1 regulation of a variety of cell death, survival and metabolic pathways. We are currently using ChIP-Seq analysis to identify targetable YB-1 downstream "hits" which drive these processes. Ultimately, we aim to identify druggable targets of YB-1 allowing us to establish more effective therapeutic options for the treatment of high-risk MB.